Research Trends and Gaps in the Use of Animated Video Media in Arabic Learning: A Bibliometric Analysis (2014-2024) - Uqba, M Sholih Salimul; Hasanah, Mamluatul; Faisol, Faisol; Ibrahim, Faisal Mahmoud Adam (MANAZHIM, 2025)
Arabic language learning can be meaningful in various ways, one of which is applying animation media in the learning process. With the advancement of technology, animation can be an effective tool to increase students' understanding and interest in learning. Therefore, the purpose of this study is to analyze research trends in the use of animated video media in Arabic language learning as well as future research opportunities through the number of developments in research publications, the level of productivity of researchers, and research development maps. The research design used is quantitative descriptive analysis with bibliometric method assisted by VOSviewer application. The data collection technique uses the help of the Publish or Perish (PoP) application which is sourced from the Google Scholar database using the keywords “Arabic Language Learning, Media, Animated Video, Arabic Learning, Video” in the last 10 years (2014-2024). The results show that the development of research on the topic of animated media in Arabic language learning in 2014-2024 has relatively increased with the highest publication occurring in 2024 which amounted to 165 publications (33%) and the lowest in 2015 with 1 publication (0.2%). The most productive researchers on the topic are Mudinillah, A. with a total of 6 publications and Hamid, MFA. with a total of 5 publications. The publication development map based on keywords produces 6 clusters, while the development map based on the author produces 18 clusters. Some topics that can be developed based on the topic of animated media in Arabic language learning include english, interest, effect, grade, article, arabic language teacher, lack, and type.